2015
DOI: 10.1155/2015/941406
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Clinical Use of Hemochromatosis Genetic Testing

Abstract: A significant proportion of hemochromatosis genetic testing does not adhere to current guidelines and would not alter patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
(19 reference statements)
0
8
2
Order By: Relevance
“…This ''one-button order'' is a tool designed specifically for our institution, based on local ordering patterns and patient characteristics. 7 Authors from a Canadian academic tertiary medical center observed a higher number of C282Y homozygotes (8.1%) than our positivity rate of less than 3.38%, which suggests practice differences in testing threshold and detection rate. 7 At our institution, which has a large referral base, transferrin saturation appears to be superior to ferritin levels as the initial test when HFE-HH is suspected.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…This ''one-button order'' is a tool designed specifically for our institution, based on local ordering patterns and patient characteristics. 7 Authors from a Canadian academic tertiary medical center observed a higher number of C282Y homozygotes (8.1%) than our positivity rate of less than 3.38%, which suggests practice differences in testing threshold and detection rate. 7 At our institution, which has a large referral base, transferrin saturation appears to be superior to ferritin levels as the initial test when HFE-HH is suspected.…”
Section: Discussioncontrasting
confidence: 68%
“…7 Authors from a Canadian academic tertiary medical center observed a higher number of C282Y homozygotes (8.1%) than our positivity rate of less than 3.38%, which suggests practice differences in testing threshold and detection rate. 7 At our institution, which has a large referral base, transferrin saturation appears to be superior to ferritin levels as the initial test when HFE-HH is suspected. These differences highlight institutional variability and the need for institution-specific interventions.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…A second cohort of patients was obtained following a systematic chart review of patients submitted for hemochromatosis genetic testing to Hamilton Health Sciences, of which routine HFE genetic testing results have been published . Inclusion criteria were biochemical evidence of iron overload (transferrin saturation >55% or ferritin >450 μg/L) and that the patient had been submitted for hemochromatosis genetic testing by their primary physician.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted, however, that it may not be necessary to identify all C282Y homozygotes as C282Y homozygotes without signs of iron overload seem to be at low risk of developing HH complications [ 17 ]. The trend towards increased HFE typing in individuals without biochemical signs of iron overload [ 18 ] highlights the need for the establishment of iron overload prior to genotyping for a more favourable cost-benefit ratio.…”
Section: Discussionmentioning
confidence: 99%